Cytologic study of normal canine testis - M. Santos; R. Marcos; M. Caniatti (Theriogenology, 2010)
It has been shown that cytology has a role in the diagnosis of canine infertility, but there are few reports dealing with normal cytologic features of the testis. This is in contrast with human medicine, in which the normal testicular cytology has been thoroughly described and assessed both by qualitative and quantitative approaches. This study was performed to provide a description of the normal cells in cytologic specimens of the testis and to establish ratios between cells that quantify testicular function. Six male dogs (Canis lupus familiaris) with no testicular pathology, aged 3 to 8 yr, were subjected to elected orchiectomy and included in this study. For each testis, six impression smears were obtained, air dried, and stained with a rapid Romanowsky-type stain. Specimens presented low blood contamination and a heterogeneous population of isolated or loosely packed cells, with high pleomorphism and anisokaryosis; naked nuclei, smeared chromatin, and multinucleation were frequent. The morphologic features of the normal testicular cells from spermatogonia to spermatozoa, including Sertoli and Leydig cells, were described. Cells were classified according to slightly modified criteria taken from human cytology. Simultaneously, 500 cells were counted per slide to determine the sperm index (SI) and Sertoli cell index (SEI), which were 26.6+/-3.8 and 4.2+/-0.8, respectively. In general, the cells encountered in the dog resemble those of men, although some particularities exist, such as the much larger size of the Sertoli cells, the highly vacuolated appearance of Leydig cells, or the lower SI and SEI in dogs. The descriptions and indexes defined here may assist in the interpretation of a testicular cytology